The Correlation of Serum Brain Natriuretic Peptide and Interleukin-6 with Quality of Life Using the Chronic Obstructive Pulmonary Disease Assessment Test - Ghobadi, Hassan (Med Princ Pract, 2018)
OBJECTIVE: The aim of this study was to determine the levels of serum pro-brain natriuretic peptide (pro-BNP) and interleukin (IL)-6 in patients with stable chronic obstructive pulmonary disease (COPD) and to correlate these markers with health-related quality of life using the COPD assessment test (CAT). MATERIALS AND METHODS: Serum pro-BNP and IL-6 levels were measured in 82 patients with stable COPD. Serum pro-BNP and serum IL-6 levels, pulmonary function, and oxygen saturation (SpO(2)) were measured according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage and CAT score. Also, the associations of both pro-BNP and IL-6 with the clinical parameters of patients were tested. RESULTS: The serum levels of IL-6 (7.57 [5–11.16] pg/mL) and pro-BNP (120.55 [92.89–144.20] pg/mL) were higher with enhancing disease severity based on the GOLD classification (p = 0.034 and 0.068, respectively). Also, serum levels of pro-BNP (120.55 [89.50–147.90] pg/mL) and IL-6 (6.68 [4.40–11.97] pg/mL) were increased in patients with high CAT scores (p = 0.004 and 0.017, respectively). There was a significant positive correlation between plasma pro-BNP and IL-6 levels (r = 0.332, p = 0.002). CONCLUSION: The results demonstrated that with increased severity of obstruction based on the GOLD criteria both IL-6 and pro-BNP were elevated. This increase in inflammatory markers was associated with a reduced quality of life and the severity of hypoxia. These findings indicated that lowering IL-6 and pro-BNP could be useful in the management of COPD patients.